2006
DOI: 10.1242/dev.02228
|View full text |Cite
|
Sign up to set email alerts
|

The Sonic hedgehog pathway independently controls the patterning,proliferation and survival of neuroepithelial cells by regulating Gli activity

Abstract: During CNS development, the proliferation of progenitors must be coordinated with the pattern of neuronal subtype generation. In the ventral neural tube, Sonic hedgehog acts as a long range morphogen to organise the pattern of cell differentiation by controlling the activity of Gli transcription factors. Here, we provide evidence that the same pathway also acts directly at long range to promote the proliferation and survival of progenitor cells. Blockade of Shh signaling or inhibition of Gli activity results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
162
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 58 publications
13
162
0
1
Order By: Relevance
“…These observations support a model in which Smad3 activity promotes differentiation of specific progenitor populations, particularly those in which Smad3 is highly expressed. As the Shh/Gli canonical pathway has recently been shown to contribute to the maintenance of spinal cord progenitors in a proliferative state (Cayuso et al, 2006), our results point to an additional level of Shh/TGF␤ functional antagonism in spinal cord development.…”
Section: Discussionsupporting
confidence: 60%
“…These observations support a model in which Smad3 activity promotes differentiation of specific progenitor populations, particularly those in which Smad3 is highly expressed. As the Shh/Gli canonical pathway has recently been shown to contribute to the maintenance of spinal cord progenitors in a proliferative state (Cayuso et al, 2006), our results point to an additional level of Shh/TGF␤ functional antagonism in spinal cord development.…”
Section: Discussionsupporting
confidence: 60%
“…Shh could be controlling proliferation by inducing FGF signaling and subsequently activating cyclin genes indirectly. However, it is also possible that Shh may have an FGF-independent role in regulating cell cycle progression, since it has been demonstrated that Shh is able to regulate key cyclin genes or other important cell cycle regulators, including phosphatases in different contexts (Dahmane and Ruiz i Altaba, 1999;Wallace, 1999;Wechsler-Reya and Scott, 1999;Kenney and Rowitch, 2000;Barnes et al, 2001;Kenney et al, 2003;Oliver et al, 2003;Cayuso et al, 2006;Yu et al, 2006). Recent evidence from studies in the mouse retina have shown that activation of the Hh pathway acts in a cellautonomous manner to up-regulate cyclinD1 and increase progenitor cell proliferation (Yu et al, 2006).…”
Section: Fgf and Shh Display Proliferative Effects During Retina Regementioning
confidence: 99%
“…Recent evidence from studies in the mouse retina have shown that activation of the Hh pathway acts in a cellautonomous manner to up-regulate cyclinD1 and increase progenitor cell proliferation (Yu et al, 2006). Activation of Gli3 has also been shown to cause a cell autonomous increase in the number of PH3-positive cells in the developing chick neural tube (Cayuso et al, 2006). Although our studies do not directly address whether Shh overexpression is acting cell autonomously to drive an increase in the number of PH3-positive cells in the CB/CMZ, it is likely that Hh is able to signal in the PH3-positive mitotic cells, because these cells also show immunoreactivity for Gli1 and Gli3, showing that Hh signaling ma- chinery is present in these cells (Supplementary Figure S1).…”
Section: Fgf and Shh Display Proliferative Effects During Retina Regementioning
confidence: 99%
“…Our previous HH blockade experiments suggest that the requirement for HH in ventral midbrain cell-fate specification is extinguished in almost all regions of ventral midbrain by H&H stage 13 (Bayly et al, 2007). The continued expression of HH until E7 may, therefore, have a role in cell survival, midbrain size regulation, dorsal patterning, or axon guidance (Ishibashi and McMahon, 2002;Blaess et al, 2006;Cayuso et al, 2006;Okada et al, 2006;Stoeckli, 2006).…”
Section: Midbrain/rfp Expression Of Shh Begins At E1 and Continues To E7mentioning
confidence: 99%